0D/2D CsPbBr3 Nanocrystal/BiOCl Nanoplate Heterostructure with Enhanced Photocatalytic Performance. Issue 16 (24th April 2022) - Ma, Li‐Jiao; Wu, Hui‐Qin; Chen, Bi‐Yu; Wang, Gang; Lei, Bing‐Xin; Zhang, Ding; Kuang, Dai‐Bin
Abstract: 0D‐2D p–n type CsPbBr3 /BiOCl heterojunction photocatalyst is successfully fabricated via the electrostatic self‐assembly process. On the basis of the photoluminescence and photocurrent density results, the CsPbBr3 /BiOCl composite exhibits a higher charge separation rate than pure BiOCl and CsPbBr3 . The degradation of Rhodamine B (RhB) result shows that the CsPbBr3 /BiOCl composite obtains the highest degradation rate of close to 100% within 60 min, which is significantly higher than those of pure CsPbBr3 (84.21%) and BiOCl (73.57%) because the p–n type heterojunction photocatalyst can promote the separation of photogenerated charge carriers. The free radical capture experiment demonstrates that O2 − plays a major role in the photodegradation of RhB. This study may provide insights into designing advanced photocatalysts for the clean‐ups of environmental pollutants. Abstract : A novel 0D‐2D p–n type CsPbBr3 /BiOCl heterojunction photocatalyst is successfully fabricated by the electrostatic self‐assembly process. Due to the formation of p–n junction, the photocatalytic degradation rate of RhB for CsPbBr3 /BiOCl is greatly improved to almost 100% within 60 min, which is higher than the pure CsPbBr3 (84.21%) and BiOCl (73.57%).